Effect of wavelength on propagation of high-power femtosecond laser pulses in diamond - T.V. Kononenko; E.V. Zavedeev; K.K. Ashikkalieva; V.I. Konov (Компьютерная оптика)
Abstract: Numerical modeling of the propagation of high-power femtosecond laser beams in a diamond crystal in the self-focusing mode is carried out. The wavelength of the modeled beams is varied in a wide range (400 nm, 532 nm, 800 nm, and 1064 nm), which covers the most common ultrashort laser systems. For all the wavelengths analyzed, a limitation in the growth of laser energy density inside the diamond crystal with increasing pulse energy is found. This effect has a certain similarity to the effect of optical limitation in laser filaments, but manifests itself outside the filament formation zone and is capable of equalizing the laser energy density, as well as the electron density, inside the extensive pre-focal region.